Democratic Decentralisation in India: Retrospect and Prospect - Sunny George (KILA Journal of Local Governance, 2013)
Taking into account two decades of experience in democratic decentralisation in India, this paper reflects on the achievements and challenges in establishing good local governance in the country. Notable achievements include establishing sound institutional framework for local governments, placing people and representatives of people at the centre stage, delegating functions for promoting ‘development as freedom’, and beginning a platform for social mobilisation for poverty reduction. However, considering the traditional Indian system of good governance, in terms of ‘niti’ and ‘nyaya’, India has to go a long way. There exists a need for amending the Constitution of India for introducing a ‘Local Self Government List’, for providing minimum grant-in-aid to local governments, and for restructuring the District Planning Committees